Fluorinated denture resin material for preventing dental caries and preparation method thereof
By combining modified polymethyl methacrylate, self-healing microcapsules and GA@HBN antibacterial composites, a denture resin material with self-healing, antibacterial, anti-staining and aesthetics was prepared, which solved the shortcomings of existing materials in terms of mechanical properties, antibacterial properties and aesthetics, and achieved the anti-carious effect of long-term use.
Patent Information
- Application Number
- CN202510596342.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2045-05-09
AI Technical Summary
The existing denture resin materials have shortcomings in mechanical properties, antibacterial properties, self-repair ability, anti-staining ability and aesthetics. They are difficult to match the biomechanical properties of natural teeth for a long time and cannot effectively prevent tooth decay.
Modified polymethyl methacrylate, self-healing microcapsules, GA@HBN antibacterial composite materials, nano ZrO2 and fluorosilane are used to prepare denture resin materials that are fluorinated to prevent dental caries by improving the toughness, antibacteriality, self-healing and anti-staining properties of the material, combined with DLP photocuring technology.
The denture resin material has achieved the anti-microcrack self-repair ability, wear resistance, antibacteriality, stain resistance and near-natural teeth color, extending its service life and preventing dental caries.
Smart Images

Figure BDA0005394697430000181 
Figure BDA0005394697430000191 
Figure BDA0005394697430000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of denture materials, in particular to a denture resin material for preventing tooth caries by adding fluoride and a preparation method thereof. Background Art
[0002] At present, although denture resin materials have been widely used in the field of oral restoration, they still face multiple difficulties. The mechanical properties of traditional resin substrates (such as bending strength and wear resistance) are difficult to match the biomechanical properties of natural teeth in the long term. In particular, microcracks or fractures are prone to occur under repeated chewing stress, resulting in a shortened life of the restoration. At the same time, the antibacterial properties of existing materials are insufficient and cannot effectively inhibit the colonization of oral pathogens (such as Streptococcus mutans), which may cause secondary caries or gingivitis, threatening the patient's oral health. At the aesthetic level, most resin substrates have weak staining resistance. After long-term contact with pigments such as coffee and tea, color shift is prone to occur, and their color levels are single, making it difficult to simulate the translucency and gradient tones of natural teeth, affecting the aesthetics of the restoration. In addition, existing materials lack self-repairing functions. Once microscopic damage occurs due to stress or aging, they need to rely on manual intervention for repair, which significantly increases clinical maintenance costs.
[0003] Although some modified resins have made progress in mechanical enhancement or caries prevention by adding inorganic fillers or antibacterial agents (such as nanosilver, fluoride) in recent years, these improvements often come at the expense of other properties. For example, although a high proportion of fillers increases strength, it leads to increased brittleness of the material, and the sustained release efficiency and long-term effectiveness of the antibacterial ingredients are still insufficient, and may cause cytotoxicity risks. In the field of self-repair, the existing light / heat responsive system is limited by the complexity of the oral environment, making it difficult to achieve precise triggering and efficient healing. Therefore, the market urgently needs a denture resin material with excellent mechanical properties, excellent antibacterial properties, self-repair, stain resistance, close to natural tooth color, and the ability to prevent natural teeth from developing caries. Summary of the Invention
[0004] The purpose of the present invention is to provide a denture resin material with fluoride for preventing tooth caries and a preparation method thereof, so as to solve the problems raised in the background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0007] 59.5-76.5 parts of modified polymethyl methacrylate;
[0008] 8-10 parts of self-repairing microcapsules;
[0009] GA@HBN antibacterial composite material 3.5-4.5 parts;
[0010] Nano ZrO2 2.4-3.6 parts;
[0011] 1-1.2 parts of stabilizer;
[0012] Dispersant 0.16-0.24 parts;
[0013] Compatibilizer 0.25-0.35 parts;
[0014] 0.7-0.9 parts of initiator;
[0015] Antioxidant 0.08-0.12 parts.
[0016] Furthermore, the modified polymethyl methacrylate is a PMMA-HEMA copolymer toughened and modified by hydroxyethyl methacrylate, wherein the content of hydroxyethyl methacrylate is 4-6%. The specific preparation steps are as follows:
[0017] Methyl methacrylate, hydroxyethyl methacrylate, azobisisobutyronitrile and dibutylhydroxytoluene were added into a three-necked flask and mixed, the mixture was heated to 60° C. under a nitrogen atmosphere, heated in a water bath with stirring at a speed of 300 r / min for 40-60 min, and cooled to room temperature to obtain modified polymethyl methacrylate.
[0018] Furthermore, the mass ratio of the methyl methacrylate, hydroxyethyl methacrylate, azobisisobutyronitrile and dibutylhydroxytoluene is 95:5:0.5:0.1.
[0019] It should be noted that the hydroxyl groups of hydroxyethyl methacrylate (HEMA) copolymerize with MMA to form PMMA-HEMA random copolymers. On the one hand, the regularity of the PMMA molecular chain is destroyed, the crystallinity is reduced, and the toughness is improved. At the same time, the hydroxyl groups of HEMA form intermolecular hydrogen bonds with the PMMA chain segments, disperse the stress, and cooperate with the self-healing microcapsules to inhibit the propagation of microcracks. On the other hand, the introduction of hydroxyl groups into HEMA improves the hydrophilicity. The hydrophilic surface is more unfavorable for the attachment of bacteria and fungi, and cooperates with the GA@HBN antibacterial composite material to improve the antibacterial properties.
[0020] Furthermore, the preparation method of the self-repairing microcapsules is as follows:
[0021] Urea, ammonium chloride and deionized water were added to the ethylene maleic anhydride aqueous solution, the pH was adjusted to 2.4-3.5, and the mixture was stirred at a speed of 150 r / min for 30 min. The core material and the polymerization inhibitor were added dropwise to the above solution, and the mixture was stirred at a speed of 400 r / min for 15 min. The formaldehyde solution was slowly added, and the temperature was raised to 55°C at a rate of 10°C / min. The mixture was stirred for 4 h, and the self-healing microcapsules were obtained after washing and drying.
[0022] Furthermore, the mass fraction of ethylene maleic anhydride in the ethylene maleic anhydride aqueous solution is 2.5%; the core material is 99% by mass of triethylene glycol dimethacrylate and 1% by mass of N,N-bis(2-hydroxyethyl)-p-toluidine; the mass fraction of formaldehyde in the formaldehyde solution is 37%; and the polymerization inhibitor is hydroquinone;
[0023] Furthermore, the usage ratio of the ethylene maleic anhydride aqueous solution, urea, ammonium chloride, deionized water, core material, inhibitor and formaldehyde solution is (20-30) mL: (2-3) g: (0.2-0.3) g: 100 mL: (48-72) mL: (25.2-37.8) mg: (4.64-6.96) mL.
[0024] It should be noted that the self-healing microcapsules use ammonium chloride to catalyze the interfacial polycondensation reaction of urea and formaldehyde to form methyl urea, which is further polycondensed to form a three-dimensional polyurea formaldehyde (PUF) polymer network. The polyurea formaldehyde serves as the shell material, triethylene glycol dimethacrylate monomer (TEGDMA) serves as the healing agent core material, and N,N-bis(2-hydroxyethyl)-p-toluidine (DHEPT) serves as an accelerator. When microcracks form in the material due to mechanical or thermal stress, stress concentration at the crack tip causes the microcapsule shell to rupture (the PUF shell has a lower fracture toughness than the resin matrix, ensuring that cracks preferentially penetrate the microcapsule), releasing TEGDMA and DHEPT into the crack gap. TEGDMA rapidly infiltrates and fills the crack area due to its low viscosity. DHEPT activates the benzoyl peroxide (BPO) initiator premixed in the resin matrix, triggering the free radical polymerization reaction of TEGDMA to form a cross-linked polymer network, achieving in-situ repair of the crack. This process delays crack propagation through a dynamic repair mechanism. The polymer formed after the polymerization of the repair agent bridges the two sides of the crack, rebuilding the continuity of the material and dissipating stress. On the other hand, the addition of microcapsules also improves the toughness of the material through the "crack deflection effect / pinning effect" - when the crack propagation path encounters the microcapsule, its interface causes the crack to detour or bifurcate, extending the propagation distance and consuming more fracture energy. At the same time, the compatibility design of the microcapsule shell and the resin matrix ensures uniform dispersion and avoids defects due to agglomeration. Through the synergistic effect of damage-responsive repair and energy dissipation network, this system gives the denture resin material dynamic crack resistance, which can extend the service life of the denture under cyclic loads.
[0025] Furthermore, the preparation steps of the GA@HBN antibacterial composite material are as follows:
[0026] A1. Add hexagonal boron nitride powder to an ethanol aqueous solution, stir magnetically at 200 r / min for 30 min until initially dispersed, transfer to an ultrasonic cleaner, sonicate for 24 h, centrifuge at 3000 r / min for 30 min, discard the precipitate, collect the supernatant, and freeze to obtain boron nitride;
[0027] Furthermore, in step A1, the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1, and the amount ratio of the hexagonal boron nitride powder to the ethanol aqueous solution is 1 g:100 mL;
[0028] A2. dispersing boron nitride in deionized water to obtain a boron nitride dispersion;
[0029] Furthermore, in step A2, the ratio of boron nitride to deionized water is 1 g:100 mL;
[0030] A3. Dissolve gallic acid in deionized water to obtain a GA solution, magnetically stir the solution at 500 r / min for 10 min, add the boron nitride dispersion obtained in step A2, magnetically stir the solution at 200 r / min for 24 h at 80°C, centrifuge the solution at 5000 r / min for 15 min, collect the precipitate, and freeze-dry to obtain a GA@HBN antibacterial composite material;
[0031] Furthermore, in step A3, the dosage ratio of gallic acid to deionized water is 1 g:50 mL, and the volume ratio of the GA solution to the boron nitride dispersion is 14:3.
[0032] It should be noted that nano-boron nitride, as a two-dimensional nanomaterial, is uniformly dispersed in the resin matrix due to its high modulus and layered structure, improving the rigidity of the material through stress transfer and crack pinning effects. Its lamellar structure can effectively block the crack propagation path, while dissipating impact energy through interfacial friction, significantly improving bending strength and impact resistance. The planar orientation characteristics of the nanosheets can also form a self-lubricating layer during wear, improving wear resistance. Gallic acid (GA) is a flavonoid compound with good antibacterial activity. On the one hand, GA exhibits antibacterial activity by disrupting fungal cell membrane integrity, inducing membrane lipid peroxidation through phenolic hydroxyl groups, and inhibiting the expression of key genes for Candida albicans hyphal transformation. On the other hand, GA synergistically produces reactive oxygen species with nano-boron nitride, altering mitochondrial transmembrane potential and triggering mitochondrial dysfunction. The sharp edges of nano-boron nitride can physically pierce cell membranes, creating a "nano-knife" effect. GA forms hydrogen bonds with the surface of nano-boron nitride via phenolic hydroxyl groups, achieving stable loading. The two-dimensional structure of nano-boron nitride provides GA with a high surface area carrier, slowing the dissolution of active ingredients and prolonging the antibacterial effect. Furthermore, GA's interfacial modification improves the dispersion of BNNS in the resin and reduces stress concentration defects caused by nanosheet agglomeration. The GA@HBN antibacterial composite creates a dual protection system of physical barrier and chemical biocidal activity, enhancing the mechanical properties of the denture resin while achieving long-lasting antifungal efficacy.
[0033] Furthermore, the stabilizer is a polyvinyl alcohol emulsifier.
[0034] Furthermore, the dispersant is titanate coupling agent NDZ-201.
[0035] It should be noted that titanate coupling agents can improve the dispersibility of nano-ZrO2. Nano-ZrO2 can disperse stress concentration, collaborating with other materials to improve the mechanical properties of denture resins. It can also adjust the refractive index to simulate the gloss of tooth enamel, collaborating with the fluoride layer to resist staining.
[0036] Furthermore, the compatibilizer is KH-570 silane coupling agent.
[0037] It should be noted that KH-570 silane coupling agent can improve the interfacial compatibility between GA@HBN antibacterial composite materials and resin.
[0038] Furthermore, the initiator is benzoyl peroxide.
[0039] It should be noted that when microcracks are generated, stress concentration causes the self-healing microcapsule PUF shell to rupture, releasing TEGDMA and DHEPT. DHEPT promotes the polymerization of benzoyl peroxide (BPO) and TEGDMA to form a cross-linked polymer network, which repairs the cracks in situ.
[0040] Furthermore, the antioxidant is 2,6-di-tert-butyl-p-cresol.
[0041] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0042] S1. Weigh modified polymethyl methacrylate, initiator, and antioxidant by weight, add them to a planetary mixer, and stir at 200 r / min for 10-15 min at 25°C; weigh and add GA@HBN antibacterial composite material and compatibilizer by weight, stir at 200 r / min for 1-3 min, add nano ZrO2 and dispersant, and stir at 200 r / min for 1-3 min; reduce the speed to 50 r / min, weigh and add self-healing microcapsules and stabilizer by weight, and stir for 3-5 min to obtain a premix;
[0043] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0044] Furthermore, the residual bubbles in the crude resin material in step S2 are less than 0.1%;
[0045] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, put the model together with the water-soluble PVA support into 40℃ warm water and soak for 30min until the support dissolves;
[0046] Furthermore, in step S3, the infrared thermal imager needs to be aimed at the printing area to ensure that the temperature is below 60°C. If the temperature exceeds 60°C, the printing is suspended and the light intensity is reduced or the inter-layer cooling time is increased.
[0047] S4. Prepare fluorosilane solution, immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, put it in a 60℃ oven to dry for 30-60 minutes, and put the dried model into a UV curing box, set the wavelength to 365nm, 8-12mW / cm 2 intensity, irradiate for 15-20 minutes, place in a 50°C oven for 40-80 minutes, heat the oven to 80°C and place for 90-150 minutes, and cool naturally to room temperature to obtain a denture resin material with fluoride added to prevent tooth caries.
[0048] Furthermore, in step S4, 100 mL of anhydrous ethanol was added with 0.1 g of perfluorooctyltriethoxysilane, and the mixture was stirred for 5 minutes until dissolved to obtain a fluorosilane solution.
[0049] It should be noted that the prepared fluorosilane solution needs to be sealed and protected from light, and the effect is better if it is prepared and used immediately.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] Modified polymethyl methacrylate can improve the toughness of denture resin materials, reduce brittleness, increase hydrophilicity, and reduce bacterial attachment; self-repairing microcapsules can improve the mechanical properties of denture resin materials and give them self-repairing capabilities; GA@HBN antibacterial composites can significantly improve the antibacterial properties of denture resin materials while improving their mechanical properties; nano-ZrO2 improves the mechanical properties of denture resin materials while adjusting the refractive index to simulate the gloss of tooth enamel and improve aesthetics; fluorosilane releases F - On the one hand, it promotes the remineralization of tooth enamel and forms a hydrophobic layer to reduce pigment adsorption. On the other hand, it can inhibit the acid production of Streptococcus mutans, inhibit bacterial activity, and indirectly improve antibacterial properties.
[0052] The fluoride-added denture resin material for preventing dental caries prepared by the present invention has the advantages of self-repair ability against microcracks, wear resistance, ability to prevent dental caries of surrounding natural teeth in the oral environment, antibacterial, staining resistance, and close to natural tooth color, and has great potential in the field of oral restoration materials. DETAILED DESCRIPTION
[0053] The following will be a clear and complete description of the technical solutions in the embodiments of the invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0054] (1) The preparation steps of modified polymethyl methacrylate are as follows:
[0055] 95 g of methyl methacrylate, 5 g of hydroxyethyl methacrylate, 0.5 g of azobisisobutyronitrile and 0.1 g of dibutylhydroxytoluene were added to a three-necked flask and mixed. The mixture was heated to 60° C. under a nitrogen atmosphere, heated in a water bath with stirring at a speed of 300 r / min for 40-60 min, and cooled to room temperature to obtain modified polymethyl methacrylate.
[0056] (2) The preparation method of self-repairing microcapsules is as follows:
[0057] 2.5 g of urea, 0.25 g of ammonium chloride and 100 mL of deionized water were added to 25 mL of an aqueous solution of ethylene maleic anhydride with a mass fraction of 2.5%, the pH was adjusted to 2.4-3.5, and the mixture was stirred at a speed of 150 r / min for 30 min. 31.185 g of triethylene glycol dimethacrylate, 0.315 g of N, N-bis(2-hydroxyethyl)-p-toluidine and 5.8 mL of hydroquinone were added dropwise to the above solution, and the mixture was stirred at a speed of 400 r / min for 15 min. Formaldehyde solution with a mass fraction of 37% was slowly added, the temperature was raised to 55 ° C at a rate of 10 ° C / min, and stirring was continued for 4 h. After filtration, washing and drying, self-healing microcapsules were obtained.
[0058] (3) The preparation steps of GA@HBN antibacterial composite materials are as follows:
[0059] A1. Add 0.5 g of hexagonal boron nitride powder to 50 mL of 44% ethanol aqueous solution, stir magnetically at 200 rpm for 30 min until initially dispersed, transfer to an ultrasonic cleaner, sonicate for 24 h, centrifuge at 3000 rpm for 30 min, discard the precipitate, collect the supernatant, and freeze to obtain boron nitride.
[0060] A2. Disperse 0.3 g of boron nitride in 30 mL of deionized water to obtain a boron nitride dispersion;
[0061] A3. Dissolve 2.8 g of gallic acid in 140 mL of deionized water to obtain a GA solution, and magnetically stir the solution at 500 rpm for 10 min. Add 30 mL of the boron nitride dispersion obtained in step A2, and magnetically stir the solution at 200 rpm for 24 h at 80°C. Centrifuge the solution at 5000 rpm for 15 min, collect the precipitate, and freeze-dry to obtain a GA@HBN antibacterial composite material.
[0062] Example 1
[0063] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0064] 68 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0065] 9 parts of self-repairing microcapsules;
[0066] GA@HBN antibacterial composite material 4 parts;
[0067] 3 parts of nano ZrO2;
[0068] 1.1 parts of polyvinyl alcohol emulsifier;
[0069] 2 parts of titanate coupling agent NDZ-2010;
[0070] 0.3 parts of KH-570 silane coupling agent;
[0071] 0.8 parts of benzoyl peroxide;
[0072] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0073] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0074] S1. Modified polymethyl methacrylate, benzoyl peroxide and 2,6-di-tert-butyl-p-cresol are weighed in parts by weight, added into a planetary mixer, and stirred at a speed of 200 r / min for 12 min at 25°C; GA@HBN antibacterial composite material and KH-570 silane coupling agent are weighed and added in parts by weight, stirred at a speed of 200 r / min for 3 min, nano ZrO2 and titanate coupling agent NDZ-201 are added, and stirred at a speed of 200 r / min for 3 min; the speed is reduced to 50 r / min, self-healing microcapsules and polyvinyl alcohol emulsifier are weighed and added in parts by weight, and stirred for 3 min to obtain a premixed solution;
[0075] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0076] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0077] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0078] Example 2
[0079] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0080] 59.5 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0081] 8 parts of self-repairing microcapsules;
[0082] GA@HBN antibacterial composite material 3.5 parts;
[0083] 2.4 parts of nano ZrO2;
[0084] 1 part of polyvinyl alcohol emulsifier;
[0085] Titanate coupling agent NDZ-2010.16 parts;
[0086] 0.25 parts of KH-570 silane coupling agent;
[0087] 0.7 parts of benzoyl peroxide;
[0088] 0.08 parts of 2,6-di-tert-butyl-p-cresol.
[0089] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0090] S1. Modified polymethyl methacrylate, benzoyl peroxide and 2,6-di-tert-butyl-p-cresol are weighed in parts by weight, added into a planetary mixer, and stirred at a speed of 200 r / min for 12 min at 25°C; GA@HBN antibacterial composite material and KH-570 silane coupling agent are weighed and added in parts by weight, stirred at a speed of 200 r / min for 3 min, nano ZrO2 and titanate coupling agent NDZ-201 are added, and stirred at a speed of 200 r / min for 3 min; the speed is reduced to 50 r / min, self-healing microcapsules and polyvinyl alcohol emulsifier are weighed and added in parts by weight, and stirred for 3 min to obtain a premixed solution;
[0091] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0092] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2, import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0093] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 minutes, placed in a 50°C oven for 1 hour, heated in the oven to 80°C and placed for 2 hours, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0094] Example 3
[0095] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0096] 76.5 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0097] 10 parts of self-repairing microcapsules;
[0098] GA@HBN antibacterial composite material 4.5 parts;
[0099] 3.6 parts of nano ZrO2;
[0100] 1.2 parts of polyvinyl alcohol emulsifier;
[0101] Titanate coupling agent NDZ-2010.24 parts;
[0102] 0.35 parts of KH-570 silane coupling agent;
[0103] 0.9 parts of benzoyl peroxide;
[0104] 0.12 parts of 2,6-di-tert-butyl-p-cresol.
[0105] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0106] S1. Modified polymethyl methacrylate, benzoyl peroxide and 2,6-di-tert-butyl-p-cresol are weighed in parts by weight, added into a planetary mixer, and stirred at a speed of 200 r / min for 12 min at 25°C; GA@HBN antibacterial composite material and KH-570 silane coupling agent are weighed and added in parts by weight, stirred at a speed of 200 r / min for 3 min, nano ZrO2 and titanate coupling agent NDZ-201 are added, and stirred at a speed of 200 r / min for 3 min; the speed is reduced to 50 r / min, self-healing microcapsules and polyvinyl alcohol emulsifier are weighed and added in parts by weight, and stirred for 3 min to obtain a premixed solution;
[0107] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0108] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0109] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 minutes, placed in a 50°C oven for 1 hour, heated in the oven to 80°C and placed for 2 hours, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0110] Comparative Example 1
[0111] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0112] 68 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0113] GA@HBN antibacterial composite material 4 parts;
[0114] 3 parts of nano ZrO2;
[0115] 1.1 parts of polyvinyl alcohol emulsifier;
[0116] 2 parts of titanate coupling agent NDZ-2010;
[0117] 0.3 parts of KH-570 silane coupling agent;
[0118] 0.8 parts of benzoyl peroxide;
[0119] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0120] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0121] S1. Weigh modified polymethyl methacrylate, benzoyl peroxide, and 2,6-di-tert-butyl-p-cresol in parts by weight, add them to a planetary mixer, and stir at a speed of 200 r / min for 12 min at 25°C; weigh and add GA@HBN antibacterial composite material and KH-570 silane coupling agent in parts by weight, stir at a speed of 200 r / min for 3 min, add nano-ZrO2 and titanate coupling agent NDZ-201, and stir at a speed of 200 r / min for 3 min; reduce the speed to 50 r / min, weigh and add polyvinyl alcohol emulsifier in parts by weight, and stir for 3 min to obtain a premixed solution;
[0122] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0123] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0124] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0125] The difference between this comparative example and Example 1 is that no self-repairing microcapsules are added.
[0126] Comparative Example 2
[0127] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0128] 68 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0129] 9 parts of self-repairing microcapsules;
[0130] GA@HBN antibacterial composite material 4 parts;
[0131] 1.1 parts of polyvinyl alcohol emulsifier;
[0132] 2 parts of titanate coupling agent NDZ-2010;
[0133] 0.3 parts of KH-570 silane coupling agent;
[0134] 0.8 parts of benzoyl peroxide;
[0135] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0136] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0137] S1. Weigh modified polymethyl methacrylate, benzoyl peroxide, and 2,6-di-tert-butyl-p-cresol in parts by weight, add them to a planetary mixer, and stir at a speed of 200 r / min for 12 min at 25°C; weigh and add GA@HBN antibacterial composite material and KH-570 silane coupling agent in parts by weight, stir at a speed of 200 r / min for 3 min, add titanate coupling agent NDZ-201, and stir at a speed of 200 r / min for 3 min; reduce the speed to 50 r / min, weigh and add self-healing microcapsules and polyvinyl alcohol emulsifier in parts by weight, and stir for 3 min to obtain a premixed solution;
[0138] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0139] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0140] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0141] The difference between this comparative example and Example 1 is that no nano-ZrO2 is added.
[0142] Comparative Example 3
[0143] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0144] 68 parts of polymethyl methacrylate;
[0145] 9 parts of self-repairing microcapsules;
[0146] GA@HBN antibacterial composite material 4 parts;
[0147] 3 parts of nano ZrO2;
[0148] 1.1 parts of polyvinyl alcohol emulsifier;
[0149] 2 parts of titanate coupling agent NDZ-2010;
[0150] 0.3 parts of KH-570 silane coupling agent;
[0151] 0.8 parts of benzoyl peroxide;
[0152] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0153] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0154] S1. Weigh polymethyl methacrylate, benzoyl peroxide and 2,6-di-tert-butyl-p-cresol by weight, add them into a planetary mixer, and stir at a speed of 200 r / min for 12 min at 25°C; weigh and add GA@HBN antibacterial composite material and KH-570 silane coupling agent by weight, stir at a speed of 200 r / min for 3 min, add nano ZrO2 and titanate coupling agent NDZ-201, and stir at a speed of 200 r / min for 3 min; reduce the speed to 50 r / min, weigh and add self-healing microcapsules and polyvinyl alcohol emulsifier by weight, and stir for 3 min to obtain a premixed solution;
[0155] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0156] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0157] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0158] The difference between this comparative example and Example 1 is that no modified polymethyl methacrylate is added, but unmodified polymethyl methacrylate is added as the main resin.
[0159] Comparative Example 4
[0160] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0161] 68 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0162] 9 parts of self-repairing microcapsules;
[0163] GA@HBN antibacterial composite material 4 parts;
[0164] 3 parts of nano ZrO2;
[0165] 1.1 parts of polyvinyl alcohol emulsifier;
[0166] 2 parts of titanate coupling agent NDZ-2010;
[0167] 0.3 parts of KH-570 silane coupling agent;
[0168] 0.8 parts of benzoyl peroxide;
[0169] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0170] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0171] S1. Modified polymethyl methacrylate, benzoyl peroxide and 2,6-di-tert-butyl-p-cresol are weighed in parts by weight, added into a planetary mixer, and stirred at a speed of 200 r / min for 12 min at 25°C; GA@HBN antibacterial composite material and KH-570 silane coupling agent are weighed and added in parts by weight, stirred at a speed of 200 r / min for 3 min, nano ZrO2 and titanate coupling agent NDZ-201 are added, and stirred at a speed of 200 r / min for 3 min; the speed is reduced to 50 r / min, self-healing microcapsules and polyvinyl alcohol emulsifier are weighed and added in parts by weight, and stirred for 3 min to obtain a premixed solution;
[0172] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0173] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0174] S4. Place the printed part in the UV curing box and set the wavelength to 365nm and 10mW / cm 2intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a denture resin material for preventing tooth caries.
[0175] The difference between this comparative example and Example 1 is that the printed part obtained in step S3 is not subjected to the surface fluorination treatment step of the original step S4.
[0176] Comparative Example 5
[0177] A denture resin material for preventing dental caries by adding fluoride comprises the following raw material components in parts by weight:
[0178] 68 parts of modified polymethyl methacrylate (containing 5% hydroxyethyl methacrylate);
[0179] 9 parts of self-repairing microcapsules;
[0180] 3 parts of nano ZrO2;
[0181] 1.1 parts of polyvinyl alcohol emulsifier;
[0182] 2 parts of titanate coupling agent NDZ-2010;
[0183] 0.3 parts of KH-570 silane coupling agent;
[0184] 0.8 parts of benzoyl peroxide;
[0185] 0.1 parts of 2,6-di-tert-butyl-p-cresol.
[0186] The preparation steps of a denture resin material for preventing dental caries by adding fluoride are as follows:
[0187] S1. Modified polymethyl methacrylate, benzoyl peroxide, and 2,6-di-tert-butyl-p-cresol were weighed in parts by weight, added to a planetary mixer, and stirred at a speed of 200 r / min for 12 min at 25°C; KH-570 silane coupling agent was weighed and added in parts by weight, stirred at a speed of 200 r / min for 3 min, nano-ZrO2 and titanate coupling agent NDZ-201 were added, and stirred at a speed of 200 r / min for 3 min; the speed was reduced to 50 r / min, self-healing microcapsules and polyvinyl alcohol emulsifier were weighed and added in parts by weight, and stirred for 3 min to obtain a premixed solution;
[0188] S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material;
[0189] S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, place the model together with the water-soluble PVA support in 40℃ warm water and soak for 30 minutes until the support dissolves. Aim the infrared thermal imager at the printing area and ensure that the temperature is below 60℃. If the temperature exceeds 60℃, pause printing and reduce the light intensity or increase the inter-layer cooling time.
[0190] S4. Take 100mL of anhydrous ethanol, add 0.1g of perfluorooctyl triethoxysilane, stir for 5 minutes until dissolved, and prepare a fluorosilane solution. Immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, and put it in a 60℃ oven to dry for 45 minutes. Put the dried model into a UV curing box, set the wavelength to 365nm, 10mW / cm 2 intensity, irradiated for 18 min, placed in a 50°C oven for 1 h, heated to 80°C in the oven for 2 h, and naturally cooled to room temperature to obtain a fluoride-added denture resin material for preventing tooth caries.
[0191] The difference between this comparative example and Example 1 is that the GA@HBN antibacterial composite material is not added.
[0192] The sources of materials are shown in Table 1.
[0193] Table 1
[0194]
[0195]
[0196] test:
[0197] 1. Mechanical properties
[0198] 1. Vickers hardness: ASTM D785 Plastic Rockwell Hardness Test
[0199] 2. Flexural strength and flexural modulus: ISO 20795-1 Dental denture base polymers (for dental resins)
[0200] 3. Impact strength: ISO 179-1 Plastics simply supported beam impact test
[0201] 4. Wear rate: ASTM D4060 Plastics Abrasion Resistance Test (Taber Abrasion Method)
[0202] Wear rate = mass loss / (density × sliding distance) × 100%
[0203] The test results are shown in Table 2.
[0204] 2. Antibacterial properties
[0205] 1. Antifungal rate (Candida albicans): JIS Z 2801 Antifungal performance test
[0206] 2. Bacterial inhibition rate (Streptococcus mutans, Staphylococcus aureus, Escherichia coli): "ISO 22196 Evaluation of antibacterial properties of plastic surfaces"
[0207] The test results are shown in Table 2.
[0208] 3. Color stability
[0209] Color value: ISO / TR 28642 Guide to color stability of dental materials
[0210] The test results are shown in Table 2.
[0211] Table 2
[0212]
[0213]
[0214] As can be seen from Table 2, the fluoridated denture resin materials for preventing dental caries prepared in Examples 1-3 all have relatively excellent mechanical properties, antibacterial properties and color stability.
[0215] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
[0216] Throughout the specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0217] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. A denture resin material for preventing dental caries with fluoride, characterized in that: The following raw materials are included in parts by weight: 59.5-76.5 parts of modified polymethyl methacrylate; 8-10 parts of self-repairing microcapsules; GA@HBN antibacterial composite material 3.5-4.5 parts; Nano ZrO2 2.4-3.6 parts; 1-1.2 parts of stabilizer; Dispersant 0.16-0.24 parts; Compatibilizer 0.25-0.35 parts; 0.7-0.9 parts of initiator; 0.08-0.12 parts of antioxidant; The modified polymethyl methacrylate is a PMMA-HEMA copolymer toughened and copolymerized with hydroxyethyl methacrylate, wherein the content of hydroxyethyl methacrylate is 4-6%.
2. The fluoridated denture resin material for preventing dental caries according to claim 1, characterized in that: The preparation method of the self-repairing microcapsule is as follows: Urea, ammonium chloride and deionized water were added to the ethylene maleic anhydride aqueous solution, the pH was adjusted to 2.4-3.5, and the mixture was stirred at a speed of 150 r / min for 30 min. The core material and inhibitor were added dropwise to the above solution, and the mixture was stirred at a speed of 400 r / min for 15 min. The formaldehyde solution was slowly added, and the temperature was raised to 55°C at a rate of 10°C / min. The mixture was stirred for 4 hours, and the self-healing microcapsules were obtained after washing and drying.
3. The denture resin material for preventing dental caries with fluoride according to claim 2, characterized in that: The core material comprises 99% by mass of triethylene glycol dimethacrylate and 1% by mass of N,N-bis(2-hydroxyethyl)-p-toluidine; the dosage ratios of the ethylene maleic anhydride aqueous solution, urea, ammonium chloride, deionized water, core material, polymerization inhibitor, and formaldehyde solution are (20-30) mL: (2-3) g: (0.2-0.3) g: 100 mL: (48-72) mL: (25.2-37.8) mg: (4.64-6.96) mL.
4. The denture resin material for preventing dental caries with fluoride according to claim 1, characterized in that: The preparation steps of the GA@HBN antibacterial composite material are as follows: A1. Add hexagonal boron nitride powder to an ethanol aqueous solution, stir magnetically at 200 r / min for 30 min until initially dispersed, transfer to an ultrasonic cleaner, sonicate for 24 h, centrifuge at 3000 r / min for 30 min, discard the precipitate, collect the supernatant, and freeze to obtain boron nitride; A2. dispersing boron nitride in deionized water to obtain a boron nitride dispersion; A3. Dissolve gallic acid in deionized water to obtain a GA solution, magnetically stir the solution at 500 r / min for 10 min, add the boron nitride dispersion obtained in step A2, magnetically stir the solution at 200 r / min for 24 h at 80°C, centrifuge the solution at 5000 r / min for 15 min, collect the precipitate, and freeze-dry to obtain a GA@HBN antibacterial composite material.
5. The denture resin material for preventing dental caries with fluoride according to claim 4, characterized in that: In step A1, the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1, and the usage ratio of the hexagonal boron nitride powder to the ethanol aqueous solution is 1 g:100 mL; in step A2, the usage ratio of boron nitride to deionized water is 1 g:100 mL; in step A3, the usage ratio of gallic acid to deionized water is 1 g:50 mL, and the volume ratio of the GA solution to the boron nitride dispersion is 14:
3.
6. The denture resin material for preventing dental caries with fluoride according to claim 1, characterized in that: The stabilizer is a polyvinyl alcohol emulsifier.
7. The denture resin material for preventing dental caries with fluoride according to claim 1, characterized in that: The dispersant is titanate coupling agent NDZ-201.
8. The denture resin material for preventing dental caries with fluoride according to claim 1, characterized in that: The compatibilizer is KH-570 silane coupling agent.
9. The denture resin material for preventing dental caries with fluoride according to claim 1, characterized in that: The initiator is benzoyl peroxide.
10. The method for preparing a denture resin material for preventing dental caries by fluoridation according to any one of claims 1 to 9, characterized in that: S1. Weigh modified polymethyl methacrylate, initiator, and antioxidant by weight, add them to a planetary mixer, and stir at 200 r / min for 10-15 min at 25°C; weigh and add GA@HBN antibacterial composite material and compatibilizer by weight, stir at 200 r / min for 1-3 min, add nano ZrO2 and dispersant, and stir at 200 r / min for 1-3 min; reduce the speed to 50 r / min, weigh and add self-healing microcapsules and stabilizer by weight, and stir for 3-5 min to obtain a premix; S2. The premixed liquid was transferred to a three-roll mill with a roller spacing of 50 μm and a roller speed ratio of 1:3:9, and the process was repeated three times to obtain a premixed material; the premixed material was placed in a vacuum degassing machine with a vacuum degree of -0.095 MPa and a temperature of 25° C. for degassing for 15 min to obtain a crude resin material; S3. Pour the crude resin material into the resin tank, turn on the DLP light-curing printer, select the 405nm light source, and set the light intensity to 15mW / cm 2 , import the designed model file, set the layer thickness to 50μm, and after printing, put the model together with the water-soluble PVA support into 40℃ warm water and soak for 30min until the support dissolves; S4. Prepare fluorosilane solution, immerse the printed part completely in the fluorosilane solution, let it stand at 25℃ for 30 minutes, put it in a 60℃ oven to dry for 30-60 minutes, and put the dried model into a UV curing box, set the wavelength to 365nm, 8-12mW / cm 2 intensity, irradiate for 15-20 minutes, place in a 50°C oven for 40-80 minutes, heat the oven to 80°C and place for 90-150 minutes, and cool naturally to room temperature to obtain a denture resin material with fluoride added to prevent tooth caries.
Citation Information
Patent Citations
High-strength oral denture base formed through 3D printing and preparation method of high-strength oral denture base
CN118986751A
Silver halide photothermographic dry imaging material
JP2004133255A
Reversible thermosensitive recording medium
JP2004262153A
Antistatic composite copolymer aqueous dispersion, plastic film having antistatic layer using it and material for silver salt photothermographic dry imaging
JP2004352818A